Correlation between in-line measurements of tomato ketchup shear viscosity and extensional viscosity. (March 2016) - Berta, Marco; Wiklund, Johan; Kotzé, Reinhardt; Stading, Mats
Abstract: The viscosity and shear thinning behavior are essential characteristics of tomato ketchup. A real-time monitoring of those characteristics during processing is important to obtain a good quality of the final product and to reduce production waste. This work investigates the measurement of rheological in-line flow properties of tomato ketchup, using a real-time technique that combines ultrasound velocity profiling (UVP) and pressure difference (PD) assessment. In-line data were compared to those obtained off-line using a rotational viscometer. There was a poor correlation with the Bostwick measurement, whereas the flow curves calculated from flow velocimetry data were very similar to those measured off-line. The extensional viscosity of ketchup was determined through the measurement of Hyperbolic Contraction Flow; the curve followed a trend similar to that for the shear viscosity over the deformation rate investigated. Highlights: For this case, the extensional viscosity curve correlates well with that of shear viscosity. The tomato ketchup Trouton ratio measured by HCF is surprisingly high, approximately 46. The shear viscosity in-line measurements at low flow rate are close to those carried out off-line. The yield stress in-line measurements at low pumping rates were close to those obtained using a stress-controlled rheometer. Bostwick measurements gave only one apparent shear viscosity, which roughly corresponded to the other measurements.